Nilai-Nilai Pancasila dalam Meningkatkan Sikap Nasionalisme di Sekolah Dasar - Heri Dermawan; Hepi Andi; Anita Hafman; Izzatun Nisa; Anggi Riafadilah (Journal on Education, 2022)
The purpose of this study was to determine the values ​​of Pancasila in increasing nationalism in elementary schools. The method used in this research is a library research method or approach, by examining several books, journals, proceedings, research reports, and other sources relevant to the research. Pancasila values ​​are very influential in life in Indonesia. Pancasila values ​​are divided into five precepts which are universal and objective. Pancasila is the Indonesian ideology that must be upheld properly. Good values ​​in Pancasila are the implementation of the existing culture. The implementation carried out is also in accordance with the personality of the Indonesian nation seen from customs, culture, religion, and outlook on life in the future. For this reason, knowledge of Pancasila is needed from an early age so that they can live in a society in accordance with the ideology of the Indonesian nation.